A comparative study on two selling approaches of selected fashion designers - Amurao, Liana Vianka S.
This is a comparative study on the selling approaches particularly through boutiques and consignment stores of selected fashion designers in Metro Manila. The research aimed to study the approaches in selling clothes that are practices by fashion designers. These approaches are establishing a boutique and consigning to another store. It presented the strategies used in the two selling approaches, namely market research, production, promotion, pricing and place. The research also determined and compared the advantages and disadvantages of each selling approach. It sough to provide aspiring designers additional knowledge in their choice of marketing channels to promote designer clothes. The data was gathered from eight (8) purposively-selected fashion designers who run boutiques or consign their clothes to other stores. In-depth interview were conducted using an interview guide developed by the researcher. The interview guide provided both qualitative and quantitative questions that enabled the researcher to know the considerations in selling clothes through boutique or consignment. The data gathered were tabulated to determine frequency distribution. Summaries were presented through pie and bar charts. It was found out that market research plays an important role because it is a form of of planning on how the products can be made available ion the satisfaction of the target consumers. The production strategies include custom-made and bulk production. Pricing of the products in the selling approaches differs in the production strategies utilized, overhead costs applied for the boutiques and percentage markups for consignment stores. Sales promotion is also important ion the business in order to dispose slow-moving stocks that have reached its maximum shelf life in order to minimize the length of time for return of investment. In the boutique shop, additional forms of promotion are practiced by the designers for a more direct marketing channel to the consumers. In the case of consignment stores, the designers have less influence as to how their products are marketed because it falls under the responsibilities of the consignees. The selling approach depends on how much the designer is willing to spend in terms of time and money. If her or she can source a large capital and attend to business as often as possible, it is recommended that the designer establish a boutique. According to the study, having a boutique renders the designer with m,ore freedom in product display. Also, it relatively brings about higher sales compared to consigning the products. On the other hand, if the designer has a regular job or is handling other businesses, it is recommended that he or she consign his or her products. This is more practical and flexible in terms of the demand in time and money. Also, there is less risk of bankruptcy because of less investment. For better understanding of the nature of the business an aspiring designer can possibly venture. it is recommended that observation and analysis be conducted on actual operation of a store from the product designs, visual displays, proper pricing and promotions to satisfy all the needs and demands of prospective customers leading to patronage and loyalty to the designer brand.